Genetic and phenotypic parameters for growth and lamb survival traits of Farta and their crosses with Washera sheep in northwest Ethiopia: Inputs to design of breeding programs - Abebe, A.S.; Alemayehu, K.; Gizaw, Solomon; Johansson, A.M. (Informa UK Limited, 2022)
Genetic and phenotypic parameters were estimated for various traits of Farta and their crosses with Washera sheep in northwest Ethiopia. Data collected from 2015 to 2020 on 4318 lambs were used. A number of models were evaluated, all contained the direct additive animal genetic effect and then, either the maternal genetic or permanent environment or both effects. The estimates of direct heritability for birth weight, weaning weight, pre-weaning daily gain, six-month weight, yearling weight and pre-weaning lamb survival were 0.08 ± 0.03, 0.20 ± 0.05, 0.15 ± 0.05, 0.24 ± 0.06, 0.29 ± 0.14 and 0.14 ± 0.04, respectively. The maternal heritabilities were 0.29 ± 0.05, 0.31 ± 0.05, 0.40 ± 0.05, 0.15 ± 0.57 and 0.02 ± 0.15 for weaning weight, pre-weaning daily gain, six-month weight, yearling weight and pre-weaning lamb survival, respectively. Genetic correlation between birth weight and pre-weaning lamb survival was negative (−0.36 ± 0.22), implying heavier lambs have low pre-weaning survival. For the other pairs of traits, genetic correlations ranging from 0.10 ± 0.16 between yearling weight and pre-weaning lamb survival to 0.98 ± 0.01 between weaning weight and pre-weaning daily gain were estimated. Overall, the present study showed that heritability is more likely to be overestimated if the maternal genetic and permanent environment effects are not taken into account. Parameters estimated in the current study can be used to design sheep breeding programs.